Survey of float tank operating practices - Laura Michele Suppes; Ashkahn Jahromi; Roy Vore (IWA Publishing, 2023)
Float tanks are recreational water baths with high concentrations of MgSO4 used for sensory deprivation. Documentation on standard operating practices within float tank facilities is lacking, which is useful for understanding the need for regulation. The goal of this study was to explore typical float tank operating practices by issuing a questionnaire to US float facilities on water treatment, testing, replacement and other maintenance methods. The survey was completed by 45 float tank operators across the US. Results show a spectrum of operating practices across float tank facilities and operational and risk distinctions from swimming pools and spas. To date, only one case of Pseudomonas aeruginosa associated with float tank use, and one outbreak associated with exposure to an art exhibition mimicking a float tank, have been published. Although float tanks pose a lower risk to users than swimming pools, they still pose some risk and health authorities should consider licensing float facilities. Knowledge gaps in float tank water quality best management practices were also observed. Most facilities use micron bag filtration, yet the contaminant removal efficacy of these systems is understudied. Additionally, more research is needed exploring chlorine, pH and alkalinity test kit accuracy in water with MgSO4. HIGHLIGHTS Environmental health authorities should consider licensing and inspecting float tank facilities to minimize risks associated with chemical and biological hazards on-site.; Chlorine is the most common primary disinfectant used to treat swimming pool and hot tub water but is not appropriate for use in float tanks.; More research is needed exploring the contaminant removal efficiency of micron bag filters in float tanks.;